PERENCANAAN DAN PERANCANGAN KAWASAN SUPERBLOK JATINANGOR TEMA HIGH TECH ARCHITECTURE - Rais, Muhammad Fadila; Yosita, Lucy (Jurnal Arsitektur ZONASI, 2021)
Abstract: Jatinangor Superblock is an integrated superblock complex located in the strategic area of Jatinangor education province. This design is based on the significant growth of the city in recent years. The development of satellite cities (hinterland) is one of the wise urban development concepts in overcoming the growth problems of the city of Bandung. Sumedang City as one of the hinterland cities, is trying to solve the development problem by providing increased development in the aspects of city facilities and infrastructure, settlements, offices, industry, worship, transportation and especially education. Jatinangor is one of the areas that has experienced significant regional development in Sumedang City. With the construction of the superblock in the Jatinangor sub-district it can encourage the growth of various activities in an integrated manner in an adequate container. This design aims to determine the facilities and facilities needed so that the occupants' activities can be well accommodated, Determine a good building layout in designing the Jatinangor Superblock, design the Jatinangor Superblock area which can be a solution to the problem of minimal land and mixed-used areas in urban areas and be a comfortable area and able to participate in building the surrounding area. In addition, this design also aims to resolve issues related to inadequate infrastructure so that they can be equipped so that the creativity and needs of building users can be fulfilled. The superblock design uses the High Tech Architecture theme. The application of the High Tech Architecture theme is quite flexible and can adjust the four functions contained in the Jatinangor superblock. With this planning and design, it is hoped that it will set a design precedent related to the superblock function. Keywords: Superblock, Jatinangor, High Tech Architecture Abstrak: Superblok Jatinangor merupakan kompleks superblok yang terintegrasi dan terletak di kawasan strategis provinsi pendidikan Jatinangor. Perancangan ini didasari dengan pertumbuhan kota yang signifikan dalam beberapa tahun terakhir. Pembangunan kota-kota satelit (hinterland) merupakan salah satu konsep pembangunan kota yang bijaksana dalam mengatasi permasalahan pertumbuhan kota Bandung. Kota Sumedang sebagai salah satu kota hinterland, berusaha mengatasi masalah pembangunan tersebut dengan memberikan peningkatan pembangunan pada aspek sarana dan prasarana kota, permukiman, perkantoran, industri, ibadah, transportasi dan terutama pendidikan. Kecamatan Jatinangor merupakan salah satu daerah yang mengalami perkembangan kawasan yang signifikan di Kota Sumedang. Dengan dibangunnya superblok di kecamatan jatinangor diharapkn dapat meningkatkan pertumbuhan kegiatan yang variatif secara terpadu dalam suatu wadah secara memadai.  Perancangan ini bertujuan Menentukan fasilitas-fasilitas dan sarana yang dibutuhkan sehingga aktivitas penghuni dapat terwadahi dengan baik, Menentukan tata letak bangunan yang baik dalam merancang Superblok Jatinangor, merancang kawasan Superblok Jatinangor yang mampu menjadi solusi permasalahan minimnya lahan dan kawasan mixed-used di area perkotaan dan menjadi kawasan yang nyaman dan mampu turut membangun kawasan sekitarnya. Selain itu perancangan ini juga bertujuan untuk menyelesaikan isu isu yang berkaitan dengan sarana prasarana yang kurang memadai agar dapat dilengkapi sehingga kreatifitas dan kebutuhan dari pengguna bangunan dapat tercukupi. Perancangan superblok ini menggunakan tema High Tech Architecture. Penerapan tema High Tech Architecture cukup fleksibel dan dapat menyesuaikan empat fungsi yang terdapat di dalam superblok Jatinangor. Dengan perencanaan dan perancangan ini diharapkan agar menjadi preseden desain terkait fungsi superblok. Kata kunci: Superblok, Jatinangor, High Tech Architecture